PENGARUH MODEL TTW BERBANTU MEDIA KONKRET TERHADAP HASIL BELAJAR KELAS V SEKOLAH DASAR - Hidayah, Nurul; Supratno, Haris; Rochmania, Desty Dwi (IJPSE : Indonesian Journal of Primary Science Education, 2020)
The problem that is the focus of this research is the effect of using the TTW model assisted by concrete media in thematic learning. This study aims to determine the results of the pretest and posttest in learning using the TTW model assisted by concrete media in the experimental group and the results of the pretest and posttest without applying the TTW model assisted by concrete media, and to provide an overview of the effect of using the TTW model assisted by concrete media on student learning outcomes. in thematic learning class V SDN 3 Craken. This study used an experimental method using the nonequevalent control group design with a comparative analysis technique. The data collection in this study used a written test, in which the pretest-posttest questions were similar questions made by researchers independently by passing the Likert validation test that had been carried out by lecturers and class teachers. The data analysis technique used is the T-test with normality test and hypothesis testing. For the pretest experimental group normality test 0.200 <0.375 and 0.075 <0.375 posttest, then the pretest control group normality test 0.200 <0.375 and the posttest 0.151 <0.375, which can be concluded that the two data are normally distributed. And to test the experimental group's hypothesis obtained T count 8.437 which this score is higher than the T table 2.201. Thus it can be said that Ho is rejected and Ha is accepted. From these results it can be concluded that the learning achievement before and after using the think talk write model assisted by concrete media is different.